Money and banking - Timberlake, Richard H.; Selby, Edward B. (Belmont, Calif. : Wadsworth Pub. Co., 1972)
This volume is a money and banking textbook written primarily for college students who have successfully mastered elementary course in economics. It presents orthodox principles of monetary theory and banking institutions, and it also offers some innovations that may make the subject more palatable and more easily assimilated than in traditional texts.
Includes bibliographies.
osc 28/9/17
Loans
Keywords: Money; Banks and banking